Efficient, metal-free production of succinic acid by oxidation of biomass-derived levulinic acid with hydrogen peroxide. Issue 4 (20th February 2015) - Dutta, Saikat; Wu, Linglin; Mascal, Mark
Abstract : A simple, non-fermentative, high-yielding, metal-free, chemical-catalytic pathway to succinic acid from biomass-derived levulinic acid is reported. Abstract : A practical, scalable, metal-free synthesis of succinic acid from the biomass-derived platform chemical levulinic acid is described. Treatment of levulinic acid with the inexpensive, simple oxidant hydrogen peroxide under the catalytic action of trifluoroacetic acid gives succinic acid in high yield and enables facile product isolation by simple distillation of the volatile catalyst and byproducts.